Durable polymer composites preparation with oxy-delignified banana fiber for automotive parts: A study on mechanical and thermal properties - Mulla, Abdul Mannan; Munagala, Chandan K.; Kesari, Aman K.; Raju, L. Yugender; Nagar, Harsha; Behara, Dilip K.; Aniya, Vineet (INDUSTRIAL CROPS AND PRODUCTS, 2024)
Keywords: Automotive parts; Banana fiber; Oxygen delignification; polypropylene; Twin-screw extruder

Static and dynamic properties investigation of modified polyethersulfone membrane for direct methanol fuel cell applications - Shah, Mumtaj; Mesfer, Mohammed K. Al; Nagar, Harsha (JOURNAL OF POWER SOURCES, 2024)
Keywords: Cross-link membranes; Direct methanol fuel cell; Molecular modelling

Nanocellulose-doped superabsorbent polymer for improved absorption properties in sanitary pad applications - Mandava, Srimukhi; Nagar, Harsha; Kumar, D. B. Rohini; Aniya, Vineet (International Journal of Biological Macromolecules, 2025)
An important disposable hygienic absorbent is the female sanitary napkin wherein superabsorbent polymers (SAP) are incorporated into it to increase the absorption capacity. Nevertheless, it has been discovered that SAPs have negative consequences on the environment and the user's health. The present study explores doping nanocellulose, into an acrylic acid-based SAP matrix to enhance absorption performance, leveraging nanocellulose's high surface area and hydrophilicity. Different SAP-nanocellulose compositions were tested, and characterizations like Thermogravimetric Analysis (TGA), Fourier Transform Infrared (FT-IR), Scanning Electron Microscopy (SEM), and X-ray Diffraction (XRD) confirmed the successful incorporation of nanocellulose into the SAP structure. Performance tests showed enhanced absorption properties in SAPs doped with nanocellulose compared to unmodified SAPs. The 70-30 composition significantly outperformed unmodified SAP (100-0). Free absorbency was highest for unmodified SAP, while 70-30 almost equaled in equilibrium absorbency in distilled water, but excelled in saline, simulated, and animal blood. Schott's pseudo-second-order model and Fickian diffusion were used to identify the kinetic swelling of SAP. For absorption under load, 70-30 attained 28.7 g/g in saline, a 28.91 % increase over unmodified SAP. In CRC, 70-30 exceeded unmodified SAP by 37 % in saline and 53 % in simulated blood demonstrating enhanced stability and absorbency.
Keywords: Absorption properties; Animal blood; Doping; Nanocellulose; Sanitary pads; Superabsorbent polymer

Novel extruded palm tree wood-derived activated carbon-based SrTiO3 for wastewater treatment in continuous system: evaluation of synthesis condition, LHSV, and pH - Ghandour, Raymond; Ali, Ali B. M.; Kadhum, Abdul Amir H.; Diab, M. A.; El-Sabban, Heba A.; Shah, Mumtaj; Nagar, Harsha (Inorganic Chemistry Communications, 2025)
SrTiO3 is a potential photocatalyst, while its wide band gap hinders sufficient adsorption of visible light and decreases the photocatalytic efficiency. Herein, activated carbon (AC) derived from palm tree wood was functionalized with varying weight percentages (10, 20, and 30 wt%) of SrTiO3 nanoparticles and evaluated for its efficiency in the photodegradation of Cefixime (CFX) in a continuous system. The effects of activation temperature on the morphological properties of AC, along with operational parameters such as Liquid Hourly Space Velocity (LHSV) (3, 4, and 5 h- 1) and the pH of the initial CFX solution (4, 6.5, and 9), were examined to optimize the photocatalytic performance. The photocatalyst activated at 900 degrees C with 30 wt% SrTiO3 exhibited the highest activity, and were characterized by XRD, BET, FE-SEM, and UV-Vis analyses. Optimal conditions for CFX degradation were found at pH of 6.5 and LHSV of 5 h- 1. Additionally, hydroxyl (center dot OH) and superoxide (center dot O2-) radicals were identified as key species in CFX photodegradation process. Hence, these findings contribute to the design and development of highly-active continuous photocatalytic system.
Keywords: antibiotic; Continuous Photocatalytic Degradation; environmental remediation; Risk Management; Wastewater treatment